2021
DOI: 10.1007/s40747-021-00428-4
|View full text |Cite
|
Sign up to set email alerts
|

Methods for image denoising using convolutional neural network: a review

Abstract: Image denoising faces significant challenges, arising from the sources of noise. Specifically, Gaussian, impulse, salt, pepper, and speckle noise are complicated sources of noise in imaging. Convolutional neural network (CNN) has increasingly received attention in image denoising task. Several CNN methods for denoising images have been studied. These methods used different datasets for evaluation. In this paper, we offer an elaborate study on different CNN techniques used in image denoising. Different CNN meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(80 citation statements)
references
References 125 publications
(122 reference statements)
0
48
0
Order By: Relevance
“…Denoising using CNNs has been the target of many studies 37 . While most of these models perform well on their dataset, they often have known noise amount and type in their images (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Denoising using CNNs has been the target of many studies 37 . While most of these models perform well on their dataset, they often have known noise amount and type in their images (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…25 In this context, recent studies have shown the flexibility of machine learning approaches, especially deep learning techniques and their robustness for any type of noise. 26,27 Most important, the reconstruction speed of the deep learning-based approach outperforms conventional methods. 28 The objective of this study was not to compare denoising performances of different approaches but rather to take advantage of 1 solution that is clinically viable, due to almost instantaneous results, and to investigate its clinical validation.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, the most commonly used methods for image restoration in computer vision are learned prior [ 27 ] and explicit prior [ 28 ]. Learned-prior is a simple method for training a deep convolution network to learn how to denoise images by training on a data set.…”
Section: Detailed System Architecture and Descriptionmentioning
confidence: 99%